Highly Stable Conjugated Polyelectrolytes for Water‐Based Hybrid Mode Electrochemical Transistors. Issue 19 (16th March 2017) - Zeglio, Erica; Eriksson, Jens; Gabrielsson, Roger; Solin, Niclas; Inganäs, Olle
Abstract : Hydrophobic, self‐doped conjugated polyelectrolytes (CPEs) are introduced as highly stable active materials for organic electrochemical transistors (OECTs). The hydrophobicity of CPEs renders films very stable in aqueous solutions. The devices operate at gate voltages around zero and show no signs of degradation when operated for 10 4 cycles under ambient conditions. These properties make the produced OECTs ideal devices for applications in bioelectronics. Abstract : Hydrophobic, self‐doped conjugated polyelectrolytes (CPEs) are introduced as highly stable active materials for organic electrochemical transistors (OECTs). The hydrophobicity of CPEs renders films very stable in aqueous solutions. The devices operate at gate voltages around zero and show no signs of degradation when operated for 10 4 cycles under ambient conditions. These properties make the produced OECTs ideal devices for applications in bioelectronics.